Potential Role of Biological Systems in Formation of Nanoparticles: Mechanism of Synthesis and Biomedical Applications - Rai, Mahendra; P. Ingle, Avinash; R. Gupta, Indarchand; S. Birla, Sonal; P. Yadav, Alka; A. Abd-Elsalam, Kamel (Current Nanoscience, 2013)
Nanotechnology is essentially related with the synthesis of nanoparticles of varying size and shapes. With the search of environment- friendly protocols for the synthesis of nanoparticles a diverse group of biological agents have been emerged. These biological agents are safe, eco-friendly and lead to green synthesis of nanoparticles. The present review focuses on the role of biological agent(s) towards the development of green nanotechnology, the applications of nanoparticles in different fields of science and technology, and also the toxicological effects of nanoparticles.
Keywords: diagnostics